Analisis Faktor-Faktor Jual Beli Tanah Secara di Bawah Tangan di Desa Babul Makmur - Safriani; Nouvan Moulia (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Buying and selling is something that often happens in all activities. A sale and purchase agreement is an agreement in which one party promises to deliver the goods and the other party pays the promised price. This study intends to examine the things that affect the procurement of artificial land in Babul Makmur Village. The type of research used is a descriptive approach, meaning that here it provides a specific description of the field in the form of facts found in the field and by describing the results of research obtained in the field, including: data that has been obtained from the library, then the researcher makes conclusions and recommendations from all the results that have been studied. The results showed that the things that resulted in the sale and purchase of underhanded land in Babul Makmur Village were: cultural/customary factors, trust and family factors, fast processing factors and low costs, education factors and lack of socialization. Then the registration of land at the Office of the National Land Agency is not a condition for the validity of the sale or not. So if there is an underhand sale and purchase, it is actually legally valid and the land is legally the property of the buyer.